Survival benefit of palliative gastrectomy followed by chemotherapy in stage IV gastric signet ring cell carcinoma patients: A large population‐based study. (25th August 2019) - Shi, Tao; Song, Xueru; Liu, Qin; Yang, Yang; Yu, Lixia; Liu, Baorui; Wei, Jia
Abstract: Background: Stage IV gastric signet ring cell carcinoma (SRCC) is a type of malignant gastric cancer (GC) with poorer survival compared to metastatic non‐SRCC gastric cancer (NOS). However, chemotherapy alone was unable to maintain long‐term survival. This study aimed to evaluate survival benefit of palliative gastrectomy plus chemotherapy (PG+C) for metastatic gastric SRCC. Methods: We obtained data on gastric cancer patients between 2010 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database. Statistical methods included χ 2 tests, Kaplan‐Meier curves, COX models, propensity score matching (PSM) and subgroup analysis. Results: Among 27 240 gastric cancer patients included, 4638 (17.03%) were SRCC patients. The proportion of patients with younger age, female gender, poorly differentiated grade and M1 stage was higher in SRCC than in NOS ( P < .001). Multivariate analysis revealed that multiple metastatic sites (HR = 1.39, 95% CI: 1.14‐1.69, P = .001) was associated with increased mortality risk in metastatic SRCC. Median survival time was improved in metastatic SRCC receiving PG+C compared to PG/C alone (13 vs 7 months, P < .001). Notably, in subgroup analysis, 13 of 17 groups of metastatic SRCC patients with PG+C had prolonged overall survival compared to chemotherapy alone, especially for those with only one metastatic site (HR = 0.61, 95% CI: 0.51‐0.73, P < .001). Conclusions: Our results suggested that there exists at least a selective group of stage IV gastric SRCC patients, who could benefit from palliative gastrectomy followed by chemotherapy compared to chemotherapy alone. Further prospective trials are needed to support our conclusion. Abstract : Stage IV gastric signet ring cell carcinoma (SRCC) is a type of malignant gastric cancer with higher metastasis rate and poorer overall survival compared to non‐SRCC gastric cancer (NOS). There exists at least a selective group of stage IV gastric SRCC patients, who could benefit from palliative gastrectomy followed by chemotherapy compared to chemotherapy alone.